2012
DOI: 10.1016/j.ecoleng.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics in a peatland forest riparian buffer zone and implications for the establishment of planted saplings

Abstract: mitigation measure in these circumstances. The aim of this paper was to assess the nutrient 28 content and phosphorus (P) adsorption capacity of the soil, and survival of planted saplings in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Dissolved reactive phosphorus leaching from degrading brash material to the underlying soil has been measured in many studies (Stevens et al, 1995;Väänänen et al, 2007;Rodgers et al, 2010;Finnegan et al, 2012). On the same study site, Finnegan et al (2012) found that DRP concentrations 13 were significantly higher under 5 year-old brash mats in the RB than in the adjacent SF,…”
Section: Discussionmentioning
confidence: 66%
“…Dissolved reactive phosphorus leaching from degrading brash material to the underlying soil has been measured in many studies (Stevens et al, 1995;Väänänen et al, 2007;Rodgers et al, 2010;Finnegan et al, 2012). On the same study site, Finnegan et al (2012) found that DRP concentrations 13 were significantly higher under 5 year-old brash mats in the RB than in the adjacent SF,…”
Section: Discussionmentioning
confidence: 66%
“…However, natural riparian zones not only release less nitrogen directly to adjacent waters, they can absorb nitrogen moving downhill and reduce nitrogen inputs to the water from disturbed uphill systems (Sweeney and Newbold 2014;Weller and Baker 2014). Natural riparian vegetation may also be more difficult to invade than other shoreline land uses with reduced vegetative cover and disturbed soils (Bertness et al 2002;DeSimone et al 2010;Finnegan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The forest run-off had a pH of 7.57 and a DRP concentration of 1.10 mg P L -1 . The total phosphorus (TP) concentration of forest run-off is usually around 1 mg L -1 (Finnegan et al, 2012), whereas DSW has a TP concentration of 20 to 100 mg L -1 and a total nitrogen (TN) concentration of to mg L -1 (Minogue et al, 2015). The DSW used in this study had a pH of 7.79 and a DRP concentration of 10.64 mg P L -1 .…”
Section: Influent and Effluent Water Characterisation And Rapid Small-scale Column Studymentioning
confidence: 99%